Primary Health Care Vital Signs Profile Assessment for Colombia - World Bank Group (World Bank, Washington, DC, 2021)
Since the first case of COVID-19 was confirmed, on March 6, 2020, the Primary Health Care (PHC) system in Colombia has been on trial, displayinga variability in governance capacity across the national territory. The response of the Colombian health system to COVID-19 and the role that PHChas played highlight several of its strengths and weaknesses. Barriers to access to health services related to distance and cost perceived by the Colombian population have steadily decreased since 2010, while barriers corresponding to perceived quality of services have remained relativelyconstant. Although barriers have been reduced and the availability of services has increased in the Health Service Delivery Institutions (HSDI) of the country, aspects related to the quality of care they provide continue to show weaknesses such as in the continuity of care, adherence of providers to clinical guidelines and aspects of patient safety. In the system, inequities of access, quality and coverage of PHC services persist throughout the national territory. To achieve a high-performing PHC system, this report proposes a series of recommendations, including: (a) Implement a new model of care focused on PHC, which offers a comprehensive package of services and reflects the health needs of the population; (b) Prepare the next generation of technicians and health professionals in PHC to work in multidisciplinary teams, and (c) Use PHC as a strategy to reduce inequities in health.